Analysis of visually handicapped patients attending outpatient department of a tertiary eye care hospital for visual disability certification in North Bihar - Agrawal, Vironika; Kumar, Nishant; Shahnawaz, Asif; Priya, Seepee; Patel, Deepak (International Journal of Research in Medical Sciences, 2025)
Background: This study aimed to analyse the demographic details, causes and severity of visual disability of the patients coming for Visual Disability Certificate in North Bihar. Methods: A retrospective study including patients applied for visual disability certificates between January 2023 and August 2024 (20 months) was performed from medical record of tertiary centre in North Bihar. The demographics, aetiologies, grades and classification of visual impairment according to the new guidelines provided in the Gazette of India published in 2018 of the study subjects were analyzed. Results were compared with data from studies on blindness certificates and population-based studies. Results: Out of total, 104 patients eligible for 40% or above visual disability certification of which 66 patients were males. The age range was 1-90 years with the maximum number of patients in 11-20 years range. According to the grade and percentage of disability, low vision grade 3c (60%) was most commonly seen in 28.92% of individuals followed by 3a (40%). Blindness 4a and 4b (90-100%) was seen in 40 patients (38.46%). Most common cause for visual disability found was glaucomatous optic atrophy followed by retinitis pigmentosa and fundal coloboma. Conclusions: Analysis of blindness certificates provides valuable information regarding different causes of visual disability and provides an insight into the overall trends in visual disability profile and help in rehabilitation.